Quantify therapeutic efficacy of buteyko breathing technique on pulmonary functions in chronic obstructive pulmonary disease athletes - KARTHIKEYAN T, (International Journal of Pharma and Bio Sciences, 2017)
The Buteyko concept is a system of breathing exercises originally devised in the 1950s by Professor Konstantin Buteyko, a Russian physician and academician. COPD is characterized by symptoms of breathlessness, wheeze, cough, sputum production and exercise intolerance. Breathlessness is principally an outcome of poor oxygen exchange. The aim of the study is to identify the efficacy of BBT in management of chronic obstructive pulmonary disease (COPD) athletes. According to American Thoracic Society Guideline for COPD diagnosis, COPD athletes in the age group 25-40years were recruited for the study. COPD athletes referred by pulmonologist were initially assessed those who met inclusion and exclusion criteria where considered for this study.. Prior to data obtained, the participation of the athletes is oriented to the study and informed consent taken through written consent form. Instructions on how to perform the spirometer test was demonstrated to the athletes. FVC, FEV1, respiratory rate and heart rate were evaluated.. After three weeks of regular daily exercise session final readings were taken.The Resultof the data obtained were analyzed by using paired t-test to find out the difference in pre and post spirometric evaluation for FVC and FEV1 along with heart rate and respiratory rate. Pre and post comparison shows p<0.05 means there is significant improvement in respiratory rate and heart rate.The present study which concluded that the Buteyko breathing exercise which is highly significant efficacy for the management of COPD among the athletes.